Sistem Pendukung Keputusan Pemilihan Konsentrasi Mata Kuliah dengan Metode MOORA - Sihombing, Daniel Oktodeli (Journal of Computer System and Informatics (JoSYC), 2024)
This study was conducted to provide decision recommendations in choosing a concentration of courses for students based on their academic performance. The problem in this research is how students can choose a course concentration for themselves based on the academic performance they have previously achieved. The selection of this concentration is calculated based on the prerequisite courses that have been previously determined for each concentration of courses using the MOORA (Multi-Objective Optimization on the Basis Of Ratio Analysis) method. Each prerequisite course is a criterion that is given a weighting using the Rank Sum weighting technique. The alternatives used in this study were 32 alternatives, all of which were students who had completed all prerequisite courses and would choose a concentration of courses in the coming semester. The results of the implementation of the MOORA method in a decision support system with Rank Sum weighting for each criterion obtained results of 18 students recommended in the Emerging Technology concentration and 14 students recommended in the Software Engineering concentration according to their academic performance. The results of the comparison between decision recommendations with the MOORA method and the questionnaire of concentration choices according to student interests showed a level of conformity of 59.38%. Thus, the decision support system with the MOORA method can provide recommendations for choosing a concentration of courses based on previously achieved academic performance.